Synthesis and characterization of bio‐based intumescent flame retardant and its application in polyurethane. (13th July 2020) - Xing, Yalin; Li, YanQiu; Lin, Zhaojun; Ma, Xiao; Qu, Hao; Fan, Ruilan
Summary: A novel bio‐based P‐N containing intumescent flame retardant melamine starch phytate (PSTM) was prepared via the reaction of phytic acid starch ester with melamine and characterized by Fourier transform infrared, scanning electron microscopy and thermogravimetric analysis (TGA). The effects of PSTM on thermal properties and flammability of rigid polyurethane (PU) foams were analyzed by TGA, limit oxygen index (LOI), vertical burning tests (UL‐94) and cone calorimeter measurement. The TGA results demonstrated that the thermal stabilities of PU/PSTM foam at high temperature was enhanced with the increasing additive amount of PSTM. The results showed that PU foam with 30 php PSTM (PU/PSTM‐30%) observed an LOI value of 25.9 and a UL‐94 rating of V‐0. Cone calorimetry data showed that peak heat release rate, total heat release and smoke production rate of PU/PSTM‐30% were distinctly lower than that of pure PU. Further experimental results demonstrated that PSTM promotes well charring of PU which could protect the foam from combustion. This work developed a novel bio‐based intumescent flame retardant by suing phytic acid and starch as the acid source and carbon source, respectively, which is of great significance to the preparation of environmental‐friendly flame retardants.